The association between teacher acceptance and sense of authenticity as mediated by peer acceptance in Japanese adolescent boys and girls - Aktar, Rumana; Sugiura, Yuko; Hiraishi, Kenji (Penerbit Universiti Kebangsaan Malaysia, 2020)
Adolescents’ sense of authenticity is a pervasive urge in positive youth development. Empirical evidence on the correlates of adolescents’ sense of authenticity in the school settings is still scarce. This study examined the relationship between teacher acceptance and a sense of authenticity in adolescent students, as mediated by peer acceptance. A total of 603 Japanese junior high school students (61% boys; Mage = 13.95 years, SD= 0.85) responded to the Child version of Teacher Acceptance-Rejection Questionnaire (Child TARQ), the Peer Acceptance Scale, and the Sense of Authenticity Scale. The structural equation modeling analyses showed that teacher acceptance contributed to students’ sense of authenticity directly, and peer acceptance partially mediated this relationship. These relationships were invariant across adolescent boys and girls. Our findings suggest that increased attention, care, nurturance, and support from teachers can lead to more peer acceptance in school, which in turn promotes adolescents’ sense of authenticity. These findings provide useful indications for school professionals and the design of intervention programs for adolescents.